PEMANFAATAN FERMENTASI AMPAS TEBU UNTUK PENGEMBANGAN ENERGI ALTERNATIF NON FOSIL DALAM BENTUK BIOETHANOL PADAT - Olla Kemala Dyani; Firra Rosariawari (EnviroUS, 2021)
Bioethanol is a potential alternative fuel because it has renewable sources. Bioethanol has physical properties that are liquid, colorless, volatile, and flammable. From the less practical physical properties of bioethanol, a change is made to solid bioethanol so that it is safe in storage and has wider use. This study aims to determine the ability of bagasse as an alternative in solid bioethanol production, to determine the tendency of the relationship between fermentation time and ethanol content in the fermentation process, to determine the effect of the weight of the compactor with the bioethanol ratio on the rate of combustion. The results of this study indicate that bagasse can be used as an alternative fuel (bioethanol) because in the fermentation process on the 6th day the resulting ethanol content is 96.8% so that it reaches SNI 7390: 2008 and the effect of a compacting agent is 200 gr in 100 gr ethanol. also has an effect in slowing down the length of the burning time so that the resulting combustion rate is smaller, valued at 74.44 gr / minute. Keywords: alternative fuels, bagasse, solid bioethanol.